Gasterointestinal helminthiasis in dairy cows in Bandung and Garut, West Java, Indonesia and its effect on milk production - Simon He; Dwi Sakti Nusantara; Anang Sujana; R. Yati Suwarti (Hemera Zoa, 1991)
Ninety seven faecal samples from lactating and nonlactating dairy cows in Bandung and Garut, West Java, were collected and examined for gasterointestinal worm eggs, in the period from August 1988 untill March 1989. At the same time of faecal collection, the daily milk production of the cows were recorded, only 5 cows (5,15%) were clean from worm eggs while the other 92 (94.85%) were found infected with one, two or three parasitic helminht classes. Three samples (3,09%) were harbouring single nematode class infections, another 3 samples (3,09%) with single cestode class infections, 23 (23,71%) single trematode class infections. Hence 29 samples (29.90%) were infected with single class helminth parasites. Two samples (2.06% ) were harbouring mixed nematode and cestode infections, 17 (17.53%) with mixed nematode and trematode and 30 (30.93%) mxed cestode and trematode infections to make up 61 samples (62.89%) harbouring two helminth class infections. Fourteen cows (14.43%) harboured mixed infections of nematode, cestode and trematode.